Potential of carrageenans in foods and medical applications - Noor, Hafizh Muhammad (Yayasan Aliansi Cendekiawan Indonesia Thailand (Indonesian Scholars' Alliance), 2018)
Background: Carrageenans, the polysaccharides obtained by extraction of certain species of red seaweeds (Rhodophyceae), have been widely used in both food industry and medical applications because of their excellent physical functional properties that are used as gelling, thickening and stabilizing agent. Several studies showed biological properties of carrageenans such as antiviral, anticoagulant, antitumor, antioxidant, anti-inflammatory and immunemodulatory activity.Aims: This study is to bring a short overview of the potential of carrageenans in foods and medical applications based on their biological activities.Methods: This short overview used relevant works and articles examined that collected through several electronic database including PubMed, Science Direct, Springer Link and Google Scholars for the years 1991-2018 with full text in English.Results: This study is an alternative approach that is necessary in order to present the potential of carrageenans in foods and medical applications.The advantages of carrageenans as a food additive and pharmaceutical formulation lie on their high availability, low cost, and low induction of resistance.Conclusion: This review suggested that carrageenans are suitable to be applied in many kinds of food products as gelling and thickening agent with their antioxidant potency as well as medical applications such as pharmaceutical formulations in drug delivery and experimental medicine. However, more comprehensive studies on toxicity and side effect of carrageenans are necessary. Keywords: Carrageenan, Antiviral, Antitumor, Antioxidant, Food and medical application Received: 19 January 2018, Reviewed: 10 May 2018, Received: in revised form 10 June 2018, Accepted: 27 June 2018. DOI: https://doi.org/10.35898/ghmj-22188